2021
DOI: 10.3389/fonc.2020.632813
|View full text |Cite
|
Sign up to set email alerts
|

LINC00667 Sponges miR-4319 to Promote the Development of Nasopharyngeal Carcinoma by Increasing FOXQ1 Expression

Abstract: Accumulating evidence has indicated that lncRNAs regulate various biological and pathological processes in diverse malignant tumors. The roles of LINC00667 in cancer development have been explored in glioma, hepatocellular carcinoma and non-small cell lung cancer, but not in nasopharyngeal carcinoma (NPC). In the present study, we characterize the role and molecular mechanism of LINC00667 in NPC progression. It was found that LINC00667 was overexpressed in NPC cells compared to normal cells. Silencing LINC0066… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Mechanistically, lncRNAs mainly regulate target gene expression by adsorbing miRNAs. For instance, LINC00667 promotes NPC progression by adsorbing miR-4319, increasing levels of forkhead box Q1 (FOXQ1) [ 18 ]. MSC antisense RNA 1 (MSC-AS1) exacerbated NPC progression by adsorbing miR-524-5p to upregulate nuclear receptor subfamily 4 group A member 2 (NR4A2) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, lncRNAs mainly regulate target gene expression by adsorbing miRNAs. For instance, LINC00667 promotes NPC progression by adsorbing miR-4319, increasing levels of forkhead box Q1 (FOXQ1) [ 18 ]. MSC antisense RNA 1 (MSC-AS1) exacerbated NPC progression by adsorbing miR-524-5p to upregulate nuclear receptor subfamily 4 group A member 2 (NR4A2) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, LINC00667 stimulates migration, invasion, and proliferation in cells pertaining to esophageal cancer by mediating the sponge axis miR-200b-3p/SLC2A3 [ 19 ]. LINC00667 up-regulates FOXQ1 by combining with miR-4319 in a competitive manner, hence facilitating the malignant phenotype of nasopharyngeal carcinoma cells [ 20 ]. It was found that LINC00667 silencing restrained the proliferation, migration and angiogenesis of non-small cell lung cancer cells ex vivo .…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA AY promoted HCC metastasis by inducing ITGAV transcription [ 37 ], and lncRNA-PDPK2P promoted the progression of HCC via PDK1/AKT/caspase 3 axis [ 38 ]. It has been reported that LncRNA LINC00667 is upregulated in many kinds of cancers such as colorectal cancer [ 39 ] and lung cancer [ 40 ] as well as nasopharyngeal carcinoma [ 41 ]. However, the roles of LINC00667 in HCC remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%